Alternative for the Treatment of Leachates Generated in a Landfll of Norte de Santander–Colombia, by Means of the Coupling of a Photocatalytic and Biological Aerobic Process (2020)
In the present study, the use of heterogeneous photocatalysis TiO2/UV coupled to an activated sludge reactor was evaluated as an alternative treatment for the leachate coming from a Landfll, located in Cucuta (Colombia). TiO2 (Degussa P-25) between 100 and 600 mg.L−1 was used as a catalyst, semi-continuous type reactors for the photocatalysis, a batch for the biological stage, UV light with accumulated energies from 20 to 60 kJ.L−1 were also used, a constant concentration of H2O2 was used as an adjuvant in all tests. The research consisted of four main phases: leachate characterization, biological treatment, optimization of photocatalytic and AOP-biological coupling. For the optimization of the photocatalytic step, an experimental design was carried out through the statistical program Statgraphics Centurion XV of factorial type 3^2 (3 levels 2 variables), modeling the results by means of a response surface, the variables of the pH and the concentration of the catalyst were included, having this as input for the response of interest the percentage (%) of DOC removal. The biological process itself provided a removal of 38 and 24% for COD and DOC, respectively. The AOP-biological coupling provided a removal of 68 and 76% in terms of COD and DOC, respectively. Thus, the coupling signifcantly improves the overall efciency of the process by more than 50%, which represents a promising improvement compared to the removal of organic matter for the treatment of the same type of water using only the biological process. The results show a viable alternative for the treatment of leachate because higher removal levels are achieved in residence times, which are considered shorter than the ones in conventional processes.